Ruthenium-Catalyzed Oxidative Dearomatization of N-Boc Indoles - Chen, Xia; Zhou, Xiao-Yu; Feng, Xiu-Juan; Bao, Ming (Synthesis, 2020)
Ruthenium-catalyzed oxidative dearomatization of N-Boc indoles for the synthesis of indolin-3-ones is described. The N-Boc indoles can be transformed into indolin-3-ones in acetonitrile, using RuCl3·3H2O as catalyst and sodium periodate (1.5 equiv) as oxidant. Further, a possible mechanism has been proposed on the basis of control experiments.
Keywords: ruthenium; oxidative dearomatization; indoles; indolin-3-ones; sodium periodate